Ceremonial and the Representation of Female Queenship between Exception and Everyday Life - De Caprio, Francesca (Sensus Historiae, 2026)
The wedding journey of Marie Louise Gonzaga Nevers from France to Poland, undertaken between November 1645 and March 1646, represents one of the most complex and significant episodes in seventeenth century European political culture and provides a privileged observatory for analysing the ways in which female queenship is constructed and represented between the exceptional dimension and everyday practices of power.